Efficient mesoporous carbon-based solid catalyst for the esterification of oleic acid. (15th January 2015) - Gao, Zhenhua; Tang, Shaokun; Cui, Xili; Tian, Songjiang; Zhang, Minhua
Graphical abstract: Highlights: Sulfonated ordered mesoporous carbons (S-OMCs) were synthesized under moderate conditions. S-OMCs were used in the esterification of oleic acid and methanol with high activity. The mechanism of the selectivity of methyl oleate was proposed. Abstract: Ordered mesoporous carbons (OMCs) with hexagonal structure and hydrophobic surface were synthesized via cooperative self-assembly of phenolic resol and surfactant F127 in ethanol, followed by sulfonation with 4-aminobenzenesulfonic acid and isoamyl nitrite. The sulfonated OMCs (S-OMCs) were used as the catalyst for the esterification of oleic acid and methanol to simulate the deacidification of oil materials with high acid values in biodiesel production. The influences of sulfonation conditions including temperature, mass ratio of the reactants and calcination temperature of OMCs on the conversion of oleic acid in the esterification reaction were investigated and the selectivity of this esterification was studied for the first time. It shows that the mesoporous carbon-based solid catalyst exhibits high activity and reusability. The conversion of oleic acid can reach up to 96.25% and the catalyst can be reused for at least nine times without remarkable loss of catalytic activity.